Understanding knowledge, attitude and perception of Rift Valley fever in Baringo South, Kenya: A cross-sectional study. - Tatenda Chiuya; Eric M Fevre; Sandra Junglen; Christian Borgemeister (Public Library of Science (PLoS), 2023)
Rift Valley fever (RVF) is a mosquito-borne viral hemorrhagic disease that affects humans and livestock. In Kenya, the disease has spread to new areas like Baringo County, with a growing realization that the epidemiology of the virus may also include endemic transmission. Local knowledge of a disease in susceptible communities is a major driver of prevention and control efforts. A cross-sectional survey using a semi-structured questionnaire was conducted in five locations of Baringo South that had reported RVF cases during the last outbreak, to determine the knowledge, attitude and perception of the predominantly agro-pastoralist community to RVF. Knowledge of RVF clinical signs, transmission, risk factors and prevention all contributed to the total knowledge score. Additionally, the respondents' attitude was based on their awareness of the threat posed by RVF and preparedness to take appropriate measures in case of suspected infection. Out of the 300 respondents, 80% had heard about the disease, however, only 9.6% attained at least half of the total knowledge score on RVF. Nevertheless, 86% recognized the threat it posed and knew the appropriate action to take in suspected human and livestock cases (positive attitude). Factors significantly associated with a better knowledge of RVF included higher education level, being Maasai, higher socio-economic index, old age and history of RVF in household members and livestock. Being Maasai and a higher socio-economic index were significantly associated with a positive attitude. The low level of knowledge exhibited by the respondents could be due to progressive loss of interest and information associated with a prolonged inter-outbreak period. This calls for regular awareness campaigns. More emphasis should also be put on educating communities on the role played by the mosquito vector in the epidemiology of RVF. The most promising routes of disseminating this information are radio and community gatherings.